Personal Factor on Perception and Motivation In The Shifting of Shopping Pattern From Traditional to Modern Markets - Pramiarsih, Euis Eka; Lisnawati, Cucu (The International Journal of Business Review (The Jobs Review), 2020)
The growth of modern markets (supermarket) has big influence on traditional markets, especially regarding their consumers. Therefore the purposes of this research are analyzing the influence of personal factor to perception and motivation in purchasing tendency from traditional market to modern market. The research was using survey method with 257 respondents (modern market consumer) which are selected by accidental respondent method. Collected data then proceed to be analyzed by Structural Equation Modeling (SEM) model utilizing AMOS Software Ver. 18.0. The result shows that personal factor significantly and positively influencing perception but negative and insignificant to the motivation of household shopping pattern from traditional market to modern market in Makassar, South SulawesiKeywords : personal, perception, and motivation factorÂ